Korean Cultural Diplomacy: Uniting Society Through Soft Power - Iwan Gunawan (Jurnal Info Sains : Informatika dan Sains, 2024)
Soft power is persuasive power that is not military or economic in nature, but is rooted in the attractiveness of culture, values and a positive image of a country. South Korea has successfully utilized soft power through the Korean wave to increase its presence and influence on the global stage. This research aims to investigate the role of Korean cultural diplomacy in integrating and uniting the international community through the concept of soft power. This research uses a qualitative approach with descriptive methods. The research results show that South Korea's cultural diplomacy, especially through the Korean Wave, has succeeded in creating a significant positive impact. The research highlights the contribution of the Korean Wave in strengthening South Korea's positive image at the global level, building sociocultural and economic ties in the East Asian region, and generating economic growth through increasing the popularity of Korean products and lifestyle. Full support from the government, including through the establishment of public institutions, provides a strong foundation for the success of South Korea's cultural diplomacy. In conclusion, research shows that South Korea's cultural diplomacy is an effective instrument in building positive connectivity, advancing the economy, and shaping global views of this country.